2003
DOI: 10.1182/blood-2002-02-0532
|View full text |Cite
|
Sign up to set email alerts
|

Early blast clearance by remission induction therapy is a major independent prognostic factor for both achievement of complete remission and long-term outcome in acute myeloid leukemia: data from the German AML Cooperative Group (AMLCG) 1992 Trial

Abstract: Risk assessment in acute myeloid leukemia (AML) using pretreatment characteristics may be improved by incorporating parameters of early response to therapy. In the 1992 trial of the German AML Cooperative Group (AMLCG), the amount of residual leukemic blasts in bone marrow was assessed one week after the first induction course (day 16 blasts). A total of 449 patients 16 to 76 years of age (median, 53 years) with de novo AML entered the trial and were evaluable. Treatment included TAD/HAM (thioguanine, cytosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
183
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 251 publications
(192 citation statements)
references
References 48 publications
5
183
1
3
Order By: Relevance
“…In a GOELAMS study of over 800 patients with AML, patients with 5 or >5% marrow blasts achieved overall CR rates, 5-year event free survival (EFS), relapse free survival (RFS) and overall survival (OS) rates of 92 vs. 69% (P < 0.0001), 48 vs. 25% (P < 0.0001), 53 vs. 37% (P 5 0.0016), and 55 vs. 36% (P < 0.0001), respectively [13]. In the German AML Cooperative Group (AMLCG) 1992 trial, day 16 blast percentage (<10 vs. 10%) significantly correlated with CR rate (P < 0.0001), EFS (P < 0.0001), RFS (P < 0.0049), and OS (P < 0.0001) [1].…”
Section: Confirmation Of Chemosensitivitymentioning
confidence: 96%
See 1 more Smart Citation
“…In a GOELAMS study of over 800 patients with AML, patients with 5 or >5% marrow blasts achieved overall CR rates, 5-year event free survival (EFS), relapse free survival (RFS) and overall survival (OS) rates of 92 vs. 69% (P < 0.0001), 48 vs. 25% (P < 0.0001), 53 vs. 37% (P 5 0.0016), and 55 vs. 36% (P < 0.0001), respectively [13]. In the German AML Cooperative Group (AMLCG) 1992 trial, day 16 blast percentage (<10 vs. 10%) significantly correlated with CR rate (P < 0.0001), EFS (P < 0.0001), RFS (P < 0.0049), and OS (P < 0.0001) [1].…”
Section: Confirmation Of Chemosensitivitymentioning
confidence: 96%
“…Early bone marrow (BM) evaluation (during aplasia or at "day 14") in patients with AML undergoing conventional induction therapy has been adopted from clinical practice in pediatric lymphoblastic leukemia (ALL) [1,2]. While it has been shown that early persistence of AML correlates with decreased complete remission (CR) rates and overall survival (OS), unlike in ALL, there are no data to indicate that early initiation of salvage therapy positively influences outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The timing was established on the basis of previous observations, which did clearly demonstrate that patients with absence or low blast count D15 BM, which reflects major sensitivity to induction therapy, had a significantly better clinical outcome when compared with those of persistent leukemia [13][14][15][16]. As DI, we decided to use the FLAG regimen, which has been proven as useful and safe for poor prognosis AML as well as for high-risk MDS.…”
Section: Resultsmentioning
confidence: 99%
“…Prognostic evaluation of cytogenetics was made according to UK Medical Research Council criteria [19]. Favorable karyotype included t(8;21) and inv (16) [20]. In all cases, diagnosis was confirmed by immunophenotypic study, as previously described [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation